(untitled) (Research, Society and Development, 2024)
Every year, more people are affected by disasters caused by hydrological and geomorphological process in Brazil. Climate change scenarios point to a worsening of this situation, mainly affecting the most vulnerable population. In order to obtain representative statistical data and vulnerability indicators to support different risk management strategies, we present a preliminary census cartographic database for the whole of Brazil: the Areas of Operational Interest (AOIs) for hydrogeomorphological risk. The AOIs are a territorial grid used exclusively to activate specific questions in the Census questionnaire, based on a spatially controlled opening. A total of 12,726 AIOs were produced throughout Brazil, with an area to be covered by the census collection of 620.9 km², which corresponds to approximately 1.2% of Brazil’s urban areas. The vast majority of AIOs occur on land that is highly vulnerable to dangerous hydrological processes (263.51km²) and landslides (113.75km²). 1,546,176 geocoded address records were identified in the National Register of Addresses for Statistical Purposes (CNEFE), the vast majority (84%) of which are private households. These households correspond to 1.4% of all census private households in Brazil in 2022. It is hoped that specific census information on the vulnerability of the population in AIOs will support priority actions in the social and economic spheres for the implementation of regional public policies that promote harm reduction throughout the country.